Serotonin transporter gene methylation is associated with hippocampal gray matter volume. Issue 11 (23rd May 2014) - Dannlowski, Udo; Kugel, Harald; Redlich, Ronny; Halik, Adriane; Schneider, Ilona; Opel, Nils; Grotegerd, Dominik; Schwarte, Kathrin; Schettler, Christiane; Ambrée, Oliver; Rust, Stephan; Domschke, Katharina; et al.
Abstract Background The serotonin transporter (5‐HTT) and the 5‐HTTLPR/rs25531 polymorphisms in its gene (SLC6A4) have been associated with depression, increased stress‐response, and brain structural alterations such as reduced hippocampal volumes. Recently, epigenetic processes including SLC6A4 promoter methylation were shown to be affected by stress, trauma, or maltreatment and are regarded to be involved in the etiology of affective disorders. However, neurobiological correlates of SLC6A4 promoter methylation have never been studied or compared to genotype effects by means of human neuroimaging hitherto Methods Healthy subjects were recruited in two independent samples (N = 94, N = 95) to obtain structural gray matter images processed by voxel‐based morphometry (VBM8), focusing on hippocampal, amygdala, and anterior cingulate gyrus gray matter structure. SLC6A4 promoter methylation within an AluJb element and 5‐HTTLPR/rs25531 genotypes were analyzed in view of a possible impact on local gray matter volume Results Strong associations of AluJb methylation and hippocampal gray matter volumes emerged within each sample separately, which in the combined sample withstood most conservative alpha‐corrections for the entire brain. The amygdala, insula, and caudate nucleus showed similar associations. The 5‐HTTLPR/rs25531 showed no main effect on gray matter, and the effect of methylation rates on hippocampal structure was comparable among the genotype groups Conclusions Methylation within the AluJb appears to have strong effects on hippocampal gray matter volumes, indicating that epigenetic processes can alter brain structures crucially involved in stress‐related disorders. Different ways of regulating SLC6A4 expression might involve exonization or transcription factor binding as potentially underlying mechanisms, which, however, is speculative and warrants further investigation. Hum Brain Mapp 35:5356–5367, 2014. © 2014 Wiley Periodicals, Inc.